E-business model conceptualization - Perechuda, Kazimierz (Zarządzanie strategiczne w dobie cyfrowej gospodarki sieciowej, 2020)
In the paper are presented the following issues: differentiations between traditional and digital business models, appropriateness of the management methods in the context of e-business models, essence of the dynamic business models, content problems of the e-business, conceptualization of the virtual business model, incorporation processes of the e-business model in the traditional industries.